Pasireotide is more effective than octreotide in reducing hepatorenal cystogenesis in rodents with polycystic kidney and liver diseases1. Issue 1 (6th March 2013) - Masyuk, Tatyana V.; Radtke, Brynn N.; Stroope, Angela J.; Banales, Jesús M.; Gradilone, Sergio A.; Huang, Bing; Masyuk, Anatoliy I.; Hogan, Marie C.; Torres, Vicente E.; LaRusso, Nicholas F.
Abstract In polycystic liver (PLD) and kidney (PKD) diseases, increased cyclic adenosine monophosphate (cAMP) levels trigger hepatorenal cystogenesis. A reduction of the elevated cAMP by targeting somatostatin receptors (SSTRs) with octreotide (OCT; a somatostatin analog that preferentially binds to SSTR2) inhibits cyst growth. Here we compare the effects of OCT to pasireotide (PAS; a more potent somatostatin analog with broader receptor specificity) on: (1) cAMP levels, cell cycle, proliferation, and cyst expansion in vitro using cholangiocytes derived from control and PCK rats (a model of autosomal recessive PKD [ARPKD]), healthy human beings, and patients with autosomal dominant PKD (ADPKD); and (2) hepatorenal cystogenesis in vivo in PCK rats and Pkd2WS25/‐ mice (a model of ADPKD). Expression of SSTRs was assessed in control and cystic cholangiocytes of rodents and human beings. Concentrations of insulin‐like growth factor 1 (IGF1) and vascular endothelial growth factor (VEGF) (both involved in indirect action of somatostatin analogs), and expression and localization of SSTRs after treatment were evaluated. We found that PAS was more potent (by 30%‐45%) than OCT in reducing cAMP and cell proliferation, affecting cell cycle distribution, decreasing growth of cultured cysts in vitro, and inhibiting hepatorenal cystogenesis in vivo in PCK rats and Pkd2WS25/‐ mice. The levels of IGF1 (but not VEGF) were reduced only in response to PAS. Expression of SSTR1 and SSTR2 (but not SSTR3 and SSTR5) was decreased in cystic cholangiocytes compared to control. Although both OCT and PAS increased the immunoreactivity of SSTR2, only PAS up‐regulated SSTR1; neither drug affected cellular localization of SSTRs. Conclusion: PAS is more effective than OCT in reducing hepatorenal cystogenesis in rodent models; therefore, it might be more beneficial for the treatment of PKD and PLD. (HEPATOLOGY 2013)